2016
DOI: 10.1111/nph.13940
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus starvation induces membrane remodeling and recycling in Emiliania huxleyi

Abstract: SummaryNutrient availability is an important factor controlling phytoplankton productivity. Phytoplankton contribute c. 50% of the global photosynthesis and possess efficient acclimation mechanisms to cope with nutrient stress. We investigate the cellular response of the bloomforming coccolithophore Emiliania huxleyi to phosphorus (P) scarcity, which is often a limiting factor in marine ecosystems.We combined mass spectrometry, fluorescence microscopy, transmission electron microscopy (TEM) and gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 83 publications
5
63
1
Order By: Relevance
“…Whether the 2P cells increase gene expression and the synthesis of P-free membrane lipids just to keep steady as cells grow in size or if the cells increase these lipid classes before P restriction is unclear. However, cell size increase as a P-stress response was observed in several other algae but not in P. tricornutum, which also showed increased SQDG synthesis and SQDG increase in cellbased calculations (Abdullahi et al, 2006;Abida et al, 2015;Peter and Sommer, 2015;Shemi et al, 2016). Cañavate et al (2017b) also saw a decline of DGDG content in N. gaditana, whereas our study showed an increase of DGDG in N. oceanica.…”
Section: P-free Lipid Synthesis During Exponential Growthcontrasting
confidence: 62%
See 3 more Smart Citations
“…Whether the 2P cells increase gene expression and the synthesis of P-free membrane lipids just to keep steady as cells grow in size or if the cells increase these lipid classes before P restriction is unclear. However, cell size increase as a P-stress response was observed in several other algae but not in P. tricornutum, which also showed increased SQDG synthesis and SQDG increase in cellbased calculations (Abdullahi et al, 2006;Abida et al, 2015;Peter and Sommer, 2015;Shemi et al, 2016). Cañavate et al (2017b) also saw a decline of DGDG content in N. gaditana, whereas our study showed an increase of DGDG in N. oceanica.…”
Section: P-free Lipid Synthesis During Exponential Growthcontrasting
confidence: 62%
“…Whether lipid classes in algae are remodeled during the transition to P limitation or if there is a switch in the synthesis of lipid classes (Brandsma, 2016), and which genes trigger these responses (Shemi et al, 2016), are unresolved questions. Our study addresses these questions and provides a comprehensive scheme for phospholipid-recycling by employing complementary lipidomic and transcriptomic data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The changed lipid composition under P‐starvation is likely derived from the fact that cells need to dissipate photosynthate and reduction equivalents by means of lipogenesis, as is also observed in other microalgae, e.g., Chlamydomonas reinhardtii (Kamalanathan et al ). Along with other phytoplankton, E. huxleyi has a highly dynamic membrane lipid composition that can be adjusted by environmental stimuli within time‐frames of 1 d, e.g., replacing phospholipids with betaine lipids during P‐starvation (van Mooy et al ; McKew et al ; Shemi et al ).…”
Section: Discussionmentioning
confidence: 99%